PENDAMPINGAN PEMBANGUNAN WEBSITE DAN KONTEN DIGITAL KREATIF DI ERA 5.0 BERBASIS GENERATIVE ARTIFICIAL INTELLIGENCE (GEN-AI) - Basuki, Setio; Faiqurrahman, Mahar; Putri, Valencia Sefiana; Nugraha, Muhammad Daffa; Shafiyah, Rahajeng Febri (Al-Umron : Jurnal Pengabdian Kepada Masyarakat, 2025)
The use of Generative Artificial Intelligence (Gen-AI) in digital content development and website development is a new approach to digital marketing in the 5.0 era. The community service program spearheaded by Universitas Muhammadiyah Malang (UMM) aims to help schools improve branding, visibility, and promotional effectiveness with AI technology that generates automated content, so that they can create websites and creative content without coding using Gen-AI. The methods used include (i) observation, (ii) digital marketing strategy development, (iii) training module development, (iv) mentoring implementation, and (v) evaluation of results. The program invited 20 teachers from three Secondary Schools. The effectiveness of this program was evaluated through questionnaires before and after mentoring, related to several aspects, namely (i) Understanding of AI, (ii) Utilization of AI to Create Text Teaching Materials (Textbooks), (iii) Utilization of AI to Create Learning Videos, (iv) Utilization of AI to Create Websites. The results showed a significant increase in the aspect of understanding of AI increased from 62% (pre-test) to 83% (post-test), utilization of AI for text teaching materials increased from 64% (pre-test) to 85% (post-test), and utilization of AI to create learning videos and websites increased from 57% (pre-test) to 82% (post-test).